ChemInform Abstract: Deep Eutectic Solvent Based on Choline Chloride and Malonic Acid as an Efficient and Reusable Catalytic System for One‐Pot Synthesis of Functionalized Pyrroles. Issue 25 (5th June 2015) - Hu, Hai‐Chuan; Liu, Yu‐Heng; Li, Bao‐Le; Cui, Zhen‐Shui; Zhang, Zhan‐Hui
Abstract: A deep eutectic solvent based on choline chloride and malonic acid is used as a dual catalyst and green reaction medium for the synthesis of a wide range of functionalized pyrroles by four‐component reaction of various amines, aldehydes, 1, 3‐dicarbonyl compounds, and nitromethane.